PERLINDUNGAN HUKUM TERHADAP KONSUMEN PRODUK PANGAN OLAHAN YANG MENGANDUNG BAHAN REKAYASA GENETIK - Suyadi Suyadi (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Obligation to write a description of genetically engineered food manunjukkan does not mean that the product of genetic engineering that use materials are not safe, but the subscription is more information, because basically the food products that have been circulating in the market is a product that is safe for consumption means that products are free from material substances that are harmful to humans and how the processing should ensure the safety of the product, therefore the information in the form of inclusion of the words